Creative LEARNING PRACTICES: A COMBINATION OF TOTAL PHYSICAL RESPONSE (TPR) : Experiment Research at Islamic Junior High School in Tangerang - Agistiawati, Eva (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2026)
Learning English as a foreign language is not easy, especially learning English in junior high school. Teachers are expected to always have creative and innovative ideas to attract students' attention in classroom learning activities so that students can understand the material being taught. Total Physical Response (TPR) is one method that can be applied. TPR is a method that uses body movements to interpret words. The objective was to help students learn English and create a pleasant classroom atmosphere such as learning by using games and songs, role plays, and storytelling, visual aids and online media and task based - learning. The method was found to be easily applicable for teachers at MTs N 4 Tangerang. The participants who attended were 37 teachers. The short lecture aims to be brief and to the point, avoiding unnecessary details or lengthy explanations. This method often uses visual aids, such as slides, diagrams or videos and interactive communication are used to enhance understanding about games and song, role plays and storytelling, visual aids or online media and task – based learning. The result of this activity was that all students were enthusiastic and easy to remember what is learned.